Dietary caloric intake and energy requirement in military personnel in the recruitment stage, Chorrillos – 2022 - J. Ortiz, Daniel (2024)
The Peruvian Army is a military institution whose objective is to control, guard, defend the national territory and participate in economic and social development. For this reason, the military requires an adequate diet to carry out these vital activities. The objective of the research is to determine the relationship between the caloric intake of the diet and the energy requirement of military personnel in their recruitment stage in Lima. It is a quantitative, descriptive and cross-sectional study. There is a sample of 80 soldiers. The sample is non-probabilistic and by convenience. The 100 % of the evaluated sample is male and their age is between 18 and 30 years old. 95 % of the sample has a high caloric intake (3 400 kcal to 2 900 kcal). 100 % of the sample presented an average total energy expenditure (TEE) in the range of (2 756.92 kcal to 2 928.42 kcal). In relation to the GET of the predictive equation of Harris Benedict 50 % presented a high energy expenditure (3 400 kcal to 2 900 kcal), with respect to Miffling 85 % a medium energy expenditure (2 899 kcal to 2 400 kcal) and with Cunningham a medium energy expenditure (2 899 kcal to 2 400 kcal), presenting in all these a significance level (p<0.05) performed by the chi-square test for both variables evaluated. It is concluded that the total energy intake presents a relationship with the three predictive equation formulas, but in the case of HB it overestimates the GET. While for this age group, the Miffling and Cunningham formulas would be recommended for their estimation of GET.